2018
DOI: 10.1126/science.aat1598
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid exposure disrupts bumblebee nest behavior, social networks, and thermoregulation

Abstract: Neonicotinoid pesticides can negatively affect bee colonies, but the behavioral mechanisms by which these compounds impair colony growth remain unclear. Here, we investigate imidacloprid’s effects on bumblebee worker behavior within the nest, using an automated, robotic platform for continuous, multicolony monitoring of uniquely identified workers. We find that exposure to field-realistic levels of imidacloprid impairs nursing and alters social and spatial dynamics within nests, but that these effects vary sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(176 citation statements)
references
References 51 publications
8
153
1
1
Order By: Relevance
“…Bumblebee colony level exposure to imidacloprid also leads to a higher number of workers going out to forage (Gill et al, 2012), a pattern that could be an adaptive response to filling a foraging deficit, but could also be maladaptive hyperactive behavior. Interestingly, Crall et al (2018) found that while chronic exposure to imidacloprid increased movement speed in nest bumblebee workers, it actually decreased the amount of time workers were active, showing similar patterns of effects to our own findings. Similarly, when investigating neonicotinoid effects on nonflight thermogenesis in bumblebees, Potts et al (2018) reported that the dose-response relationship for dietary imidacloprid exposure exhibited a biphasic hormesis, whereby low-dose stimulated warming rates and a high dose led to inhibition.…”
Section: Discussionsupporting
confidence: 88%
“…Bumblebee colony level exposure to imidacloprid also leads to a higher number of workers going out to forage (Gill et al, 2012), a pattern that could be an adaptive response to filling a foraging deficit, but could also be maladaptive hyperactive behavior. Interestingly, Crall et al (2018) found that while chronic exposure to imidacloprid increased movement speed in nest bumblebee workers, it actually decreased the amount of time workers were active, showing similar patterns of effects to our own findings. Similarly, when investigating neonicotinoid effects on nonflight thermogenesis in bumblebees, Potts et al (2018) reported that the dose-response relationship for dietary imidacloprid exposure exhibited a biphasic hormesis, whereby low-dose stimulated warming rates and a high dose led to inhibition.…”
Section: Discussionsupporting
confidence: 88%
“…Colony-wide, high-resolution tracking augments larger-scale measures such as weight 55 and can be combined with additional hive sensors for a novel surveillance system 56 . The automatic nature of our approach also facilitates the imaging of multiple hives 57 , an important consideration due to colony-to-colony variability.…”
Section: Discussionmentioning
confidence: 99%
“…Pupae thermoregulation appears to be functionally significant in honeybees because even a slight deviation from optimal temperature impairs pupal development and the performance of the emerging adults (Groh et al 2004;Tautz et al 2003). In bumblebee colonies, the brood temperature is typically kept at 28-32°C throughout the day (Crall et al 2018;Vogt 1986). The strong effect of pupae on sleep, together with the indications that incubation is increased at night in bumblebees at the expanse of sleep, suggest that brood incubation is one of the factors that drive nurses to reduce their sleep.…”
Section: Discussionmentioning
confidence: 99%